(untitled) (Eurasian Journal of Ecology, 2016)
Investigated a functional condition of cardiovascular system at students before hypoxemic-giperkapnichesky trainings. It is known that under the influence of systematic respiratory and physical exercises reserve opportunities of an organism increase. By results of adaptation potential at students after hypoxemic-giperkapnichesky trainings improvement of a functional condition of cardiovascular system was noted.